Numerical study on the combustion characteristics of a fuel-centered pintle injector for methane rocket engines. (June 2017) - Son, Min; Radhakrishnan, Kanmaniraja; Yoon, Youngbin; Koo, Jaye
Abstract: A pintle injector is a movable injector capable of controlling injection area and velocities. Although pintle injectors are not a new concept, they have become more notable due to new applications such as planet landers and low-cost engines. However, there has been little consistent research on pintle injectors because they have many design variations and mechanisms. In particular, simulation studies are required for bipropellant applications. In this study, combustion simulation was conducted using methane and oxygen to determine the effects of injection condition and geometries upon combustion characteristics. Steady and two-dimensional axisymmetric conditions were assumed and a 6-step Jones–Lindstedt mechanism with an eddy-dissipation concept model was used for turbulent kinetic reaction. As a result, the results with wide flame angles showed good combustion performances with a large recirculation under the pintle tip. Under lower mass flow-rate conditions, the combustion performance got worse with lower flame angles. To solve this problem, decreasing the pintle opening distance was very effective and the flame angle recovered. In addition, a specific recirculation zone was observed near the post, suggesting that proper design of the post could increase the combustion performance, while the geometry without a recirculation zone had the poor performance.